2018
DOI: 10.1089/mdr.2017.0379
|View full text |Cite
|
Sign up to set email alerts
|

Porin Deficiency in Carbapenem-ResistantEnterobacter aerogenesStrains

Abstract: Porin deficiency plays an important role in carbapenem resistance among clinical E. aerogenes isolates under regulation of the sRNAs micC and micF. Furthermore, overexpression of micC and micF had a minor to no impact on carbapenem minimum inhibitory concentrations, and thus, the regulatory mechanism is likely to be complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
2
28
1
1
Order By: Relevance
“…Thus, further studies are needed to understand the pathways of regulation for resistance-related genes in K. pneumoniae during antibiotic pressure. A recent study revealed that in vitro carbapenem resistance induction could lead the loss of OmpK 36 in induced isolate after several days of serial passaging [51]. In this study, we reported a link between a 14-day imipenem treatment and the loss of OmpK 36 in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, further studies are needed to understand the pathways of regulation for resistance-related genes in K. pneumoniae during antibiotic pressure. A recent study revealed that in vitro carbapenem resistance induction could lead the loss of OmpK 36 in induced isolate after several days of serial passaging [51]. In this study, we reported a link between a 14-day imipenem treatment and the loss of OmpK 36 in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, further studies are needed to understand the pathways of regulation for resistance-related genes in K. pneumoniae during antibiotic pressure. A recent study revealed that a 13-day in vitro carbapenem resistance induction showed loss of OmpK 36 in mutant isolate [21]. In current study, our data showed that a 14-day treatment in vivo of MDR K. pneumoniae infection was not particularly effective in clearing MDR K. pneumoniae the sputum.…”
Section: Discussioncontrasting
confidence: 46%
“…The regulation systems are also responsible for a rapid adaptation following external stresses such as antibiotics, chemicals, and colicins 1,6 . It should be stressed that only few studies have studied a possible role of MicF and MicC in the alteration of OM permeability in resistant strains [145][146][147] In the case of uncharged molecules, electro-osmosis can be considered 148 Computer modelling can nowadays predict the energy barrier of a molecule along the channel axis which allows to obtain an estimate for the flux. In the above figure we show the free-energy surface of avibactam along the Z axis of diffusion and, for a comparison with free energies of Cl−and Na+ ions, calculated using their relative densities with respect to the bulk.…”
Section: Discussionmentioning
confidence: 99%